The Effect of Foreign Ownership and Financial Leverage on Tax Avoidance with Audit Quality as Moderating Variables - MUJI, Muji; WALUYO, Waluyo (PT Keberlanjutan Strategis Indonesia, 2024)
Manufacturing companies are the largest contributor to tax revenue in Indonesia. However, this group experienced negative tax revenue growth when in general there was growth in tax revenue. The existence of foreign ownership and the use of debt (financial leverage) is suspected to be one of the causes of tax avoidance by the company even though it has been audited by an external party. The study was conducted using Moderated Regression Analysis on 124 manufacturing companies listed on the Indonesia Stock Exchange. The results showed that foreign ownership had no significant effect on tax avoidance, while financial leverage had a significant effect on tax avoidance. In addition, audit quality does not moderate significantly the influence of foreign ownership and financial leverage.